Ethical Approach to Sustainability Accounting Practices and Financial Performance of Aviation Companies in Nigeria: A Conceptual Model - Okafor, Uchenna Israel (Society & Sustainability, 2022)
Considering the significance of environmental and social hazards alongside the inevitable economic importance of the aviation industry, the researcher examined the general impact of the ethical approach to environmental and social Sustainability Accounting Practices (SAP) on their performance in Nigeria. Due to a lack of financial data in the public domain of Nigeria’s aviation industry to empirically measure performance indices, the researcher adopted an exploratory research design in combination with an integrative conceptual and a practical case review as alternative analytical models. The case result and majority of findings among reviewed researches conducted in other countries did not only support a positive association between sustainability accounting practices and financial performance of aviation companies but also demonstrated a significant influence of the ethical dimension of SAP in such nexus. Drawing from the results of reviewed studies and findings from case analysis, therefore, the researcher hypothetically concluded that a positive association exists between SAP and financial performance in Nigeria's aviation industry. However, the researcher further attributed the scarcity of relevant financial data for empirical analysis to a poor listing of aviation companies on the Nigerian Stock Exchange (NSE), especially the domestic airlines. In addition to developing a hypothetical background and raising research questions for future empirical investigation, it was recommended among other things that aviation companies in Nigeria should exploit the ethical dimension of corporate social responsibility as a practical strategy for entrenching their "going concern" objective in a long-term good corporate financial outlook.